Impact of Product Quality and Brand Image on Purchase Decision for LGNSHOP Fashion Products - Handayani, Nur; Sutawijaya, Ahmad Hidayat (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to examine the impact of product quality and brand image on purchasing decisions of LGNShop fashion products, to uses a quantitative method with a survey involving 120 respondents who have used and purchased LGNShop products. The analysis results indicate that product quality and brand image have a positive and significant impact on purchasing decisions. Product quality is assessed based on high-quality materials, attractive designs, and product durability, while brand image is evaluated through effective marketing campaigns and good customer service. This study concludes that improving product quality and managing a good brand image will positively affect consumer purchasing decisions. The implication of this research is that LGNShop needs to continuously improve product quality and maintain a positive brand image to strengthen consumer trust and loyalty. Keywords: Product Quality, Brand Image, Purchasing Decision, Fashion Products, LGNShop